2009
DOI: 10.3109/10715760903407293
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin supplementation does not alter antioxidant status in humans

Abstract: This study measured the influence of ingesting quercetin on plasma measures for oxidative stress and antioxidant capacity. Male and female subjects (n = 1002) varying in age (18-85 years) and body mass index (BMI) (16.7-52.7 kg/ m2) were studied. Subjects were randomized to one of three groups using double-blinded methods: placebo, 500 mg or 1000 mg quer-cetin/day with 125 mg or 250 mg vitamin C/day, respectively. Pre-and post-study fasting blood samples show that plasma quercetin increased in a dose-responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 60 publications
(96 reference statements)
2
54
0
2
Order By: Relevance
“…Ten manuscripts (Abbey & Rankin, 2011;Bigelman et al, 2010;Cheuvront et al, 2009;Cureton et al, 2009;Davis et al, 2010;Ganio et al, 2010;MacRae & Mefferd, 2006;Nieman et al, 2009;Nieman et al, 2010 ;Quindry et al, 2008) were identified, of which seven (Bigelman et al, 2010;Cureton et al, 2009;Davis et al, 2010;Ganio et al, 2010;MacRae & Mefferd, 2006;Nieman et al, 2009;Nieman et al, 2010) met the inclusion criteria. Altogether, those manuscripts provided 10 and 4 EP and VO 2max effect estimates, respectively.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten manuscripts (Abbey & Rankin, 2011;Bigelman et al, 2010;Cheuvront et al, 2009;Cureton et al, 2009;Davis et al, 2010;Ganio et al, 2010;MacRae & Mefferd, 2006;Nieman et al, 2009;Nieman et al, 2010 ;Quindry et al, 2008) were identified, of which seven (Bigelman et al, 2010;Cureton et al, 2009;Davis et al, 2010;Ganio et al, 2010;MacRae & Mefferd, 2006;Nieman et al, 2009;Nieman et al, 2010) met the inclusion criteria. Altogether, those manuscripts provided 10 and 4 EP and VO 2max effect estimates, respectively.…”
Section: Search Resultsmentioning
confidence: 99%
“…Results of human studies are somewhat less promising, showing that in healthy young subjects QS does not decrease inflammation (Nieman, Henson, Davis, Angela Murphy, et al, 2007;Nieman, Henson, Davis, Dumke, et al, 2007) and oxidative stress (McAnulty et al, 2008;Shanely et al, 2010) or improve muscle oxidative capacity (Cureton et al, 2009) and mitochondrial biogenesis (Nieman et al, 2010), but it does enhance endothelial function (Loke et al, 2008).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…During the study, subjects agreed to avoid any other supplements containing quercetin; no other restrictions were placed on diet, supplement usage, or medications. Several papers have recently been published from this large study, with a focus on quercetin supplementation effects on inflammation, oxidative stress, plasma quercetin response, immune function, and upper respiratory tract infections (Heinz et al 2010a(Heinz et al , 2010bJin et al 2010;Shanely et al 2010). All experimental procedures were approved by the Appalachian State University Institutional Review Board, and written informed consent was obtained from each subject.…”
Section: Subjectsmentioning
confidence: 99%